Bifidumbacterin Pl and Immunomodulin as Bio-Immune Correctors in Children with Salmonellosis - Otanazar Kodirovich Sadullaev, Valeriya Rustamovna Rakhmanova, Barno Sultanovna Samandarova, Shokirbek Yusupovich Zakirov, Zumrad Satimbayevna Allaberganova (International Journal of Advanced Science and Technology, 2020)
In children with diarrheal diseases living in environmentally unfavorable conditions of the Southern Aral Sea region, аdeep dysbiosis occurs, which is manifested by a sharp decrease in the indigenous microflora. Upon admission to the hospital, dysbiotic changes in the intestinal microflora practically did not differ in children under 7 years of age from patients with bacterial dysentery, salmonellosis, coli enteritis and diarrhea of another bacterial and unknown etiology in the conditions of the South Aral Sea region.According to our observations, treatment of diarrheal diseases with generally accepted antidiarrheal therapeutic methods, although it leads to some improvement in the patient’s general condition, does not have a noticeable effect on dysbiotic changes in the intestines of sick children, and apparently does not contribute to the restoration of intestinal microbiocenosis even to the level of the 2nd control group of local healthy children. Bio-immune correction of intestinal dysbiosis using Bifidumbacterin PL and Immunomodulin not only restored the gut microflora to the normal parameters of local healthy children (2nd control group), but also lead to its normalization in accordance with the figures of healthy children from Tashkent (1st control group). Restoration of obligate intestinal microflora led to a marked decrease in the number of facultative opportunistic microorganisms compared with the initial indicators. Thus, application of Bifidumbacterin PL and Immunomodulin as bio-immune correctors represents a promising therapeutic strategy for treatment of salmonellosis in children.